PIBID: construindo caminhos para prática docente em educação física - REIS, Luna Aparecida Gonçalves dos (2019)
The PIBID – Institutional Program of Scholarship to Teaching Initiation configures as an important educational public policy for the promotion of Brazilian education. It’s a project developed by the Ministry of Education, which establishes a bridge between the university and the Basic Education and assumes an integration between theory and practice by the insertion of licentiate degree students in the public schools exercising pedagogical activities, with the assistance of scholarships. a bibliographic study was carried about PIBID was held in dissertations and thesis of the Capes Databank and that it showed that 86.7% of the production is related to teacher’s formation and 12.6% to how this program interfered in teaching practice, this study had as objective to analyze the contributions of PIBID to the professional acting of the egresses of the subproject Physical Education /PIBID/UFU in the Basic Education. The research used an approach of quali-quantitative nature, composed by a bibliographical and fieldstudies with six former scholarship holders from the subproject of Physical Education / PIBID / UFU and who are currently teachers of Basic Education. They participated in a structured interview, and their answers were analyzed by the software Iramuteq. The results showed that the alumni entered the PIBID due to the affinity with the licentiate model and the interest for the area as a field of activity and the insertion in PIBID made it possible to understand the daily school life as a learning space. Regarding the experiences related to the organization of the pedagogical work, the graduates emphasized that the group relationship marked by the union, effort, partnership and mutual aid were significant. At the same time the relationship with coordinators and supervisors, the aspects that stood out were the establishment of dialogue, the respect and the valorization of collective work. The meetings of the subproject were permeated by studies and discussions around the pedagogical practice, with a highlight on planning.It was evident in the speech of the alumni that the active participation in the activities developed in the Program were configured as an anticipation of the experience inside the school space. The perception of the interviewed subjects about the PIBID’s contributions for their professional acting emphasized the great help in questions that involve planning, in the transformation of the scientific knowledge in the scholar’s knowledge and in the recognition of the Physical Education’s importance for the school, as well as the valorization of the profession. The actions promoted by the subproject Physical Education/PIBID/UFU have established a bridge between the University and Basic Education. This way, the present subproject reached the objectives proposed by the program by motivating the teacher’s formation, contributing to the valorization of teaching practices, elevating the quality of the teacher’s initial formation, promoting integration between theory and practice andbyinserting the licentiate’s student in the school’s environment, collaborating in an effective way for the teaching learning, configurating itself with a positive interference in the knowledge mobilization, contributing beyond the professional acting.